The Development of Collaborative Keys to Promote Engagement in Undergraduate Online Asynchronous Statistics Courses - Anelise Sabbag; Nicola Justice; Samuel Frame; Lauren Laundroche; Rachel Roggenkemper (Journal of Statistics and Data Science Education)
Many online courses use discussion forums to encourage active engagement and student-to-student interaction. However, discussion forum assignments often lack much of the structure, format, and accountability that is associated with high-quality student experiences and student-to-student interactions. This article uses a classroom research model to introduce, develop, and evaluate Collaborative Keys for an undergraduate student population. We will share how the Collaborative Keys were revised to facilitate cooperative learning in an asynchronous online introductory statistics course. We modified an existing social constructivism framework, the Community of Inquiry, to evaluate the essential social elements of student interactions both before and after substantial revisions were made to the Collaborative Keys based on previous investigations. The changes were done to encourage and support student-to-student interactions through the use of group collaborations rather than a whole class collaboration, individual accountability through individual answers, and support for positive interdependence between students by having a shared goal of one final answer for the group. Our initial results suggest that students were more effectively connected with their groups members and social interactions were improved using a revised version of the Collaborative Keys. Supplementary materials for this article are available online.